Asymmetric Impact of Exchange Rate Fluctuations on Money Demand in Sudan - Elhassan, Tomader (Asian Economic and Financial Review, 2021)
This study aims to examine the asymmetric impact of exchange rate fluctuations on money demand in Sudan. The non-linear autoregressive distributed lag (ARDL) model was applied to data pertaining to 1960–2018. The empirical results suggest that the impact of the exchange rate is asymmetric in the long and short terms. In the short term, a positive change in the exchange rate increases money demand, while a negative change in the exchange rate has no effect. However, in the long term, a positive change in the exchange rate increases money demand, and a negative change has the same effect. In the long term, a negative change in the exchange rate has a greater effect than a positive change, indicating that a depreciation of the Sudanese pound has a greater effect. The difference between the positive and negative changes in the exchange rate indicates its asymmetric effect on money demand in Sudan. This study recommends that monetary policy in Sudan should target such positive and negative changes in the exchange rate, and that decision makers should adopt policies that achieve exchange rate stability. In addition, policymakers should also aim to establish an industrial production base to reduce reliance on imports.